Kes1p shares homology with human oxysterol binding protein and participates in a novel regulatory pathway for yeast Golgi-derived transport vesicle biogenesis. - Fang, M (1996)
The yeast phosphatidylinositol transfer protein (Sec14p) is required for biogenesis of Golgi-derived transport vesicles and cell viability, and this essential Sec14p requirement is abrogated by inactivation of the CDP-choline pathway for phosphatidylcholine biosynthesis. These findings indicate that Sec14p functions to alleviate a CDP-choline pathway-mediated toxicity to yeast Golgi secretory function. We now report that this toxicity is manifested through the action of yeast Kes1p, a polypeptide that shares homology with the ligand-binding domain of human oxysterol binding protein (OSBP). Identification of Kes1p as a negative effector for Golgi function provides the first direct insight into the biological role of any member of the OSBP family, and describes a novel pathway for the regulation of Golgi-derived transport vesicle biogenesis.